Experimental and Finite Elements Analysis Study of Warming Effect on Deboned Force for Embedded NiTinol Wire into Linear Low Density Polyethylene - Amin, Samir Ali; Hassan, Ali Yasser (Al-Khwarizmi Engineering Journal, 2018)
This study presents the debonding propagation in single NiTi wire shape memory alloy into linear low-density polyethylene matrix composite the study of using the pull-out test. The aim of this study is to investigate the pull-out tests to check the interfacial strength of the polymer composite in two cases, with activation NiTinol wire and without activation. In this study, shape memory alloy NiTinol wire 2 mm diameter and linear fully annealed straight shape were used. The study involved experimental and finite element analysis and eventually comparison between them. This pull-out test is considered a substantial test because its results have a relation with behavior of smart composite materials. The pull-out test was carried out by a universal tensile test machine type (Laryee), load capacity (50 kN), and a test speed of 1mm/min. The finite elements modeling was performed by ANSYS V.15. The results of pull-out test showed that in the activation of NiTinol wire embedded in host matrix linear low-density polyethylene (LLDPE), the deboned force was about 74 N, but for the case without activation, it was about 106 N. Deboned shear stress for the case with activation was about 0.73 MPa, but for the case of without activation, it was about 1.05 MPa. ANSYS result for deboned shear stress in case with activation was about 0.8 MPa. As for the case of without activation, deboned shear stress was about 0.99 MPa. The activation of the ratio of deboned shear stress and deboned force decreased by 30.47% and 30.13%, respectively. The error ratio between experimental and ANSYS results was equal to 8% for the case with activation and 5.7% for the case without activation.